REPARATION SYSTEM GENES: POPULATION DIFFERENCES IN HEREDITARY OVARIAN AND BREAST CANCER DETERMINED BY NEXT-GENERATION SEQUENCING - O. I. Brovkina; M. G. Gordiev; R. F. Enikeev; M. O. Druzhkov; L. Kh. Shigapova; E. I. Shagimardanova; O. А. Gusev; V. V. Kosiy; D. S. Khodyrev; A. G. Kedrova; R. Sh. Khasanov; A. G. Nikitin (Опухоли женской репродуктивной системы, 2017)
Introduction. Development of hereditary ovarian cancer (OC) and breast cancer (BC) is caused by genetic abnormalities in the DNA reparation system consisting of more than 100 genes. However, currently in the majority of medical centers in Russia, diagnosis of hereditary OC and BC consists of determination of the most frequent mutations (8 points) in the BRCA1 and BRCA2 genes using polymerase chain reaction (PCR). Moreover, these mutations are common in Slavic population while in other populations they are rare or altogether absent.The study objective is to perform a population analysis of mutations in the reparation system genes which must be considered during chemotherapy prescription.Materials and methods. Using next-generation sequencing (NGS), we analyzed reparation system genes in 139 blood samples of Tatar female patients with hereditary OC and BC. To compare mutation rates, 67 blood samples from Slavic female patients examined at the Federal Research Clinical Center FMBA (Moscow) in 2014-2016 were analyzed by real-time PCR.Results. Real-time PCR has shown a 5382insC (NM_007300.3:c.5329dup)  mutation in 36 % of Slavic patients. The same mutation was observed only in 7 % of Tatar women. Performed NGS analysis of 139 Tatar female patients with hereditary BC and OC has identified 61 mutations in the reparation system genes, one third of which (28 %) didn’t belong to the BRCA1/BRCA2 genes.Conclusion. The NGS method allowed to identify rare mutations characterizing different ethnic groups facilitating prescription of optimal chemotherapy.